2022
DOI: 10.1097/meg.0000000000002347
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of hepatic structure and function evaluation based on vibration-controlled transient elastography and liver maximum function capacity test in patients with nonalcoholic fatty liver disease

Abstract: Background and aims Transient elastography [vibration-controlled transient elastography (VCTE)] noninvasively guides risk stratification in patients with nonalcoholic fatty liver disease (NAFLD). Patients with nonalcoholic steatohepatitis (NASH) and fibrosis can be identified using the FAST-score. The liver maximum function test (LiMAx) could be helpful in more precise risk stratification. This pilot study evaluated VCTE, FAST-score, and LiMAx in NAFLD patients. Methods NAFLD patients prospectively underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In addition, several studies have shown that the degree of hepatic steatosis calculated by liver enzymes or indices may be statistically biased and may significantly underestimate the number of participants with NAFLD in epidemiological studies ( 36 ). VCTE, as recommended by the American Gastroenterological Association for risk stratification and management of patients with NAFLD, is highly accurate in diagnosing the degree of hepatic steatosis and the degree of fibrosis ( 37 , 38 ). Therefore, we used VCTE data to avoid diagnostic inaccuracies and the inability to quantify the degree of hepatic steatosis in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have shown that the degree of hepatic steatosis calculated by liver enzymes or indices may be statistically biased and may significantly underestimate the number of participants with NAFLD in epidemiological studies ( 36 ). VCTE, as recommended by the American Gastroenterological Association for risk stratification and management of patients with NAFLD, is highly accurate in diagnosing the degree of hepatic steatosis and the degree of fibrosis ( 37 , 38 ). Therefore, we used VCTE data to avoid diagnostic inaccuracies and the inability to quantify the degree of hepatic steatosis in the current study.…”
Section: Discussionmentioning
confidence: 99%